Galaxy flybys: evolution of the bulge, disc, and spiral arms. Issue 1 (22nd June 2021) - Kumar, Ankit; Das, Mousumi; Kataria, Sandeep Kumar
ABSTRACT: Galaxy flybys are as common as mergers in low-redshift Universe and are important for galaxy evolution as they involve the exchange of significant amounts of mass and energy. In this study, we investigate the effect of minor flybys on the bulges, discs, and spiral arms of Milky Way mass galaxies for two types of bulges – classical bulges and boxy/peanut pseudo-bulges. Our N -body simulations comprise of two disc galaxies of mass ratios 10:1 and 5:1, where the discs of the galaxies lie in their orbital plane and the pericentre distance is varied. We performed photometric and kinematic bulge–disc decomposition at regular time-steps and traced the evolution of the disc size, spiral structure, bulge sersic index, bulge mass, and bulge angular momentum. Our results show that the main effect on the discs is disc thickening, which is seen as the increase in the ratio of disc scale height to scale radius. The strength of the spiral structure A 2 / A 0 shows small oscillations about the mean time-varying amplitude in the pseudo-bulge host galaxies. The flyby has no significant effect on non-rotating classical bulge, which shows that these bulges are extremely stable in galaxy interactions. However, the pseudo-bulges become dynamically hotter in flybys indicating that flybys may play an important role in accelerating the rate of secular evolution in disc galaxies. This effect on pseudo-bulges is a result of their rotating nature as part of the bar. Also, flybys do not affect the time and strength of bar buckling.